The Role of Presentations in Foreign Language Lessons for Special Purposes - Nazarov Rustam Irkinovich; Ismatulleva Iroda Izatullaevna (Researchparks Publishing, 2022)
At the same time, as our experience shows, students of non-linguistic specialties experience difficulties in organizing and conducting presentations, have poor skills in searching and processing information, and are not sufficiently fluent in the terminological vocabulary of their specialty, which, in general, negatively affects the motive reaction to the study of the subject. Therefore, it is necessary to intensify the efforts of teachers to teach students the rules for conducting presentations, show them the advantages of such learning activities, teach them the skill of communicating with an audience and prepare them for a speech. Given the relevance of the problem raised, the purpose of this report is to analyze the theoretical background and reveal the technology of presentations so that they play a teaching role in a foreign language course for special purposes.